Disentangling the effects of environmental conditions on wintering and breeding grounds on age‐specific survival rates in a trans‐Saharan migratory raptor. (26th September 2019) - Millon, Alexandre; Danovaro, Cécile; Printemps, Thierry; Leroux, Alain B.; Schlaich, Almut E.; Villers, Alexandre; Bourrioux, Jean‐Luc; Bretagnolle, Vincent
Abstract : Migratory species are subject to environmental variability occurring on breeding and wintering grounds. Estimating the relative contribution of environmental factors experienced sequentially during breeding and wintering, and their potential interaction, to the variation of survival is crucial to predict population viability of migratory species. Here we investigated this issue for the Montagu's harrier Circus pygargus, a trans‐Saharan migrant. We analysed capture–recapture data from a 29‐year long monitoring of wing‐tagged offspring and adults at two study sites in France (Rochefort‐RO and Maine‐et‐Loire‐ML). The study period covers a climatic shift occurring in the Sahel with increasing rainfall following a period of droughts (Sahel greening). We found that harriers' adult survival in RO (between 1988 and 2005) varied over time and was sensitive to the interaction between the amount of rainfall in the Sahel and the annual mean breeding success, two proxies of prey availability. The occurrence of adverse conditions on breeding and wintering grounds in the same year decreased survival from 0.70–0.77 to 0.48 ± 0.05. Juvenile survival in RO was slightly more sensitive to conditions in Europe than in the Sahel. Unexpectedly, lower survival rates were found in years with higher mean breeding success, suggesting compensatory density feedbacks may operate. By contrast, adult survival in ML, monitored between 1999 and 2017, was higher compared to RO (0.76 ± 0.03 versus 0.66 ± 0.02), remained constant and unaffected by any proxy of prey availability. This difference seems consistent with the fact that harriers in ML experienced better and especially less variable environmental conditions during breeding and wintering seasons compared to RO. Overall, we showed that survival of a migratory bird is sensitive to the level of variability in environmental conditions and that adverse conditions on wintering grounds can amplify the negative effects of conditions during the previous breeding season on birds' survival.